A Comparison of Apical Transportation in Severely Curved Canals Induced by Reciproc and BioRaCe Systems - Nabavizadeh, Mohammadreza; Abbaszadegan, Abbas; Khojastehpour, Leila; Amirhosseini, Mohsen; Kiani, Ebrahim (Iranian Endodontic Journal, 2014)
Introduction: Preserving the apical root structure during cleaning and shaping of the canal has always been a challenge in endodontics particularly when the root canals are curved. The purpose of this in vitro study was to compare the apical transportation induced by the Reciproc and BioRaCe rotary systems in preparing the mesiobuccal root canal of the human maxillary molars. Materials and Methods: The mesiobuccal canals of sixty extracted maxillary molars with curvature angle of 25-35˚ were selected and randomly assigned into two groups. Each canal was prepared by either Reciproc or BioRaCe rotary systems. A double-digital radiographic technique and AutoCAD software were used to compare the apical transportation at 0.5, 1, 2, 3, 4 and 5 mm distances from the working length (WL). The distance between the master apical rotary file and the initial K-file in the superimposed radiographs determined the amount of apical transportation. An independent t-test was used to compare the groups. The statistical significant level was set at 0.05. Results: Apical transportation of the Reciproc group was significantly greater than the BioRaCe group in all distances (P<0.001). The maximum apical transportation occurred in the Reciproc group at 0.5 mm from the WL (0.048±0.0028 mm) and the minimum occurred for BioRaCe at 5 mm from the WL (0.010±0.0005 mm). Conclusions: The Reciproc system produced significantly more apical transportation than the BioRaCe, but this fact does not seem to negatively alter the clinical success or quality of root canal treatment.<!–?xml:namespace prefix = "o" ns = "urn:schemas-microsoft-com:office:office" /–>